The Reciprocal Effect of Elevated CO2 and Drought on Wheat-Aphid Interaction System - Xie, Haicui; Shi, Fengyu; Li, Jingshi; Yu, Miaomiao; Yang, Xuetao; Li, Yun; Fan, Jia (Frontiers in Plant Science, 2022)
Due to the rising concentration of atmospheric CO2, climate change is predicted to intensify episodes of drought. However, our understanding of how combined environmental conditions, such as elevated CO2 and drought together, will influence crop-insect interactions is limited. In the present study, the direct effects of combined elevated CO2 and drought stress on wheat (Triticum aestivum) nutritional quality and insect resistance, and the indirect effects on the grain aphid (Sitobion miscanthi) performance were investigated. The results showed that, in wheat, elevated CO2 alleviated low water content caused by drought stress. Both elevated CO2 and drought promoted soluble sugar accumulation. However, opposite effects were found on amino acid content—it was decreased by elevated CO2 and increased by drought. Further, elevated CO2 down-regulated the jasmonic acid (JA) -dependent defense, but up-regulated the salicylic acid (SA)-dependent defense. Meanwhile, drought enhanced abscisic acid accumulation that promoted the JA-dependent defense. For aphids, their feeding always induced phytohormone resistance in wheat under either elevated CO2 or drought conditions. Similar aphid performance between the control and the combined two factors were observed. We concluded that the aphid damage suffered by wheat in the future under combined elevated CO2 and drier conditions tends to maintain the status quo. We further revealed the mechanism by which it happened from the aspects of wheat water content, nutrition, and resistance to aphids.